(untitled) (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2012)
Based on the analyses of the phraseological idioms in Ukrainian and German literature, the article deals with synchronous сomparing of the phraseological units with the component “nose” by structurally grammatical plan. It is defined that the difference between idioms with the component die Nase/nose in Ukrainian and English languages are shown largely in the composition, semantics and usage of some elements of structural schemes that is lexical and grammatical patterns.